BODY COMPOSITION AND BONE MINERAL DENSITY IN WOMEN WITH RHEUMATOID ARTHRITIS - S. E. Myasoedova; O. A. Rubtsova; E. E. Myasoedova (Klinicist)
Objective: to establish specific features of body composition, skeletal muscle changes and bone mineral density (BMD) in middle-aged and elderly female patients with rheumatoid arthritis (RA) as compared to female subjects without RA.Materials and methods. The study included 86 female patients with RA aged 59.06 ± 7.52 years and 81 female subjects without RA aged 57.4 ± 5.3 years. Body composition and BMD in spine and femur was assessed using Lunar Prodidgy device (General Electric). Sarcopenia was defined as lean mass index (LMI) of < 5.64 kg/m2 .Results. We have detected statistically significant decrease in fat, muscle and femoral BMD in female patients with RA as compared to their non-RA counterparts. Sarcopenia in the form of osteopenic sarcopenia and osteosarcopenia obesity was detected in 13.95 % RA patients vs 4.94 % non-RA subjects based on LMI findings. Both groups had high prevalence of osteopenia obesity.Conclusions. Assessment of the body composition by radiographic densitometry in female RA patients with osteopenia or osteoporosis may be used to detect sarcopenia and its phenotypes in order to inform prognosis and adjust the management plan.